2003
DOI: 10.1063/1.1614847
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heterogeneity on the elastic properties of auxetic materials

Abstract: Auxetic materials are gaining practical interest for their unusual and sometimes extreme mechanical response. The process of modeling these materials so far has highlighted a number of microstructural properties that are key to these materials. However these models often rely on the assumption of homogeneity and order within the materials. Practically, a homogeneous auxetic material such as foam is unlikely to be manufactured. This work seeks to analyze the effect of fluctuations within the microstructure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…A cursory glance at an auxetic foam reveals that like most materials their structure (both geometric and mechanical) vary as you move through the material. Previous work [16] begins to address the issue of disorder (heterogeneity) within auxetic materials. Other work in the context of granular materials [17] shows how important a correct use of heterogeneity is for the prediction of elastic moduli in a material with microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…A cursory glance at an auxetic foam reveals that like most materials their structure (both geometric and mechanical) vary as you move through the material. Previous work [16] begins to address the issue of disorder (heterogeneity) within auxetic materials. Other work in the context of granular materials [17] shows how important a correct use of heterogeneity is for the prediction of elastic moduli in a material with microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 20 years, materials with negative Poisson's ratios (auxetic materials), which expand laterally when stretched longitudinally, have been of significant scientific interest and have considerable practical applications [1][2][3][4][5][6]. It has been known to be theoretically possible since Love [7].…”
Section: Introductionmentioning
confidence: 99%
“…4(c) and 4(b), respectively, for dimensionless thickness h/l = 0.2 using the shear correction factor k = 5/(6 -v). Based on Koender's [34] theory for pre dicting spatial features within a heterogeneous material under a persistent strain path, Gaspar [35] and Gaspar et al [36] showed that a valid elastic moduli can be obtained if the continuum length is at least 5 mean cell grain diameters. 4(c) and 4(b) show that there exists a boundary that indicates the comparative shear-to-bending deformation ratio for both types of load distributions.…”
Section: Si (11) (31) = (13) (51) = (15) (33) (71) = (17) (5mentioning
confidence: 99%